2,2,2-Trimethyl-N-(phenylsulfonyl)acetamide - Gowda, B. Thimme (International Union of Crystallography, 2008)
The N—H and C=O bonds of the SO(2)—NH—CO group in the title compound, C(11)H(15)NO(3)S, are anti to each other. The asymmetric unit contains two independent molecules. The benzene rings form dihedral angles of 83.19 (8) and 76.01 (10)° with the mean planes of the C(2)NOS fragments. The molecules are linked into chains parallel to the b axis by intermolecular N—H⋯O hydrogen bonds.